(untitled) (Journal of the Spanish Institute for Strategic Studies, 2024)
The expansion of the sovereignty of States beyond their territorial sea is increasingly attractive in light of technological improvements and the reduction of the costs of exploitation of maritime spaces far from the coast. The four conventions signed at the first United Nations conference on the Law of the Sea in 1958 and the United Nations Convention on the Law of the Sea in 1982 are the legal basis for the delimitation of these spaces, divided according to the degree of sovereignty that the States exert on them. One of the most debated spaces is that of the continental shelf, established up to a maximum of 200 nautical miles from the limit of the territorial sea. Those coastal States whose continental shelves meet certain requirements can request the extension of their shelf up to 350 nautical miles, known as an extended shelf. The continental shelf projected by Spain in the Atlantic is not immune to these requirements, which is why the Spanish State has made three requests for expansion: in the Celtic Sea and Bay of Biscay, which includes the FISU area; in Galicia and the Area of ​​Common Interest with Portugal; and in the waters adjacent to the Canary Islands.